(untitled) (University Arena, 2025)
Chronic nonspecific lower back pain (CLLBP) is one of the most common musculoskeletal disorders affecting global functionality, posture, and quality of life. Postural retraining is essential in the management of this condition, and Pilates has become an increasingly popular approach in modern physiotherapy because of its fundamental principles such as centring, control, breathing, body alignment, and deep muscle activation. This study aimed to compare, from a theoretical perspective, the two major directions of the Pilates method: the classical approach, which faithfully preserves the original principles and exercises proposed by Joseph Pilates, and the contemporary approach, which has been adapted according to recent research in biomechanics, neuroscience, and clinical physiotherapy. Classical Pilates is based on a fixed sequence of exercises performed with strict precision and rhythmic control, with an emphasis on symmetry and uniformity. In contrast, contemporary Pilates allows for individualised adaptation of exercises according to the patient’s needs and therapeutic goals using modern equipment (for example, Reformer, Cadillac, Ledder Barrel, Spine Corrector, Exo Chair), sensory integration, and neuromotor feedback. The analysis revealed that both styles contribute to improved postural control; however, contemporary Pilates offers increased versatility, the possibility of therapeutic customisation, and more effective integration into clinical rehabilitation protocols. In the context of the recovery of patients with LCN, therapeutic adaptability is essential to respond to variability in individual symptomatology and functional limitations. This study underscores the need to develop standardised yet adaptable protocols that effectively integrate the advantages of both classical and contemporary Pilates approaches within the framework of postural rehabilitation.